Kualitas Karkas Ayam Broiler yang Diberikan Pakan Supplemen Limbah Wortel - G G Maradon; R Noviadi (PETERPAN (Jurnal Peternakan Terapan), 2020)
Carrot waste is carrots with criteria that are not suitable for human consumption. Carrot waste contains various vitamins and minerals. This study aims to evaluate the quality of broiler chicken carcass. The study used a completely randomized design (CRD) with 4 treatments and 6 replications. The treatments given included R0 = 0% additional feed from carrot waste; R1 = 0.5% additional feed waste carrots; R2 = 1% additional feed from carrot waste; R3 = 1.5% additional feed from carrot waste. The data obtained were tested for normality and homogeneity before being analyzed using the Analysis of Variants. If there is a difference then proceed with Duncan's multiple distance test. The results showed that the best results were given additional feed of carrot waste at the level of 1% to increase carcass weight and carcass percentage, carcass color would increase along with the increase in the level of carrot waste addition.